Resident Perceptions of Event Impacts: Taupo and Ironman New Zealand - Buch, Tina (Auckland University of Technology, 2007)
In New Zealand the development and promotion of sporting events is becoming increasingly popular, due in part to the role of sport in building the nation's identity, the economic benefits, and a growing awareness of the importance of health and fitness within the community. Given this increased popularity it is important that the impacts of these events upon the local 'host' communities be understood. Social impacts have been given more and more attention in recent years by event researchers, due to the recognition that the long term sustainability of such events can only be achieved with the approval and participation of residents. This research addresses these issues in the context of Taupo, New Zealand using the case of Ironman New Zealand.This thesis adopts a mixed method approach using interviews (n=7), participant observation, and a web-survey (n=111). The findings confirm that it is vital to investigate and understand impacts of events on host communities. The findings are also consistent with theories identified in the literature in terms of the nature of social impacts on host communities. The overall results indicate that residents are aware of both the positive and negative impacts of Ironman New Zealand. Respondents highlight positive impacts such as economic benefits, exposure of Taupo, community togetherness, and the encouragement of sports, yet they also recognize negative impacts such as inconvenience from traffic congestion, and road closures. Accordingly, the community was grouped into three distinct clusters with positive, negative and ambivalent perceptions, and were labelled 'Lovers', 'Pessimists' and 'Realists'. The findings further suggest that the use of web-surveying for community research is still in its infancy and needs further development enabling it to be used as an effective tool. Finally it is proposed that small to medium scale sporting event hosted in regional communities may contribute to a sense of community and to the creation of social capital. Further research is needed to confirm this proposition.
Keywords: Resident perceptions; Sporting events; Community participation; Social impacts; Web-survey